Analisa Yuridis Terhadap Upaya Pemerintah Memblokir Game Roblox Yang Mengandung Muatan Permainan Judi Online - Nino Gilang Darmawan; M.S Tumanggor; Lukman Hakim (JURNAL HUKUM PELITA, 2025)
In the modern era, with technological advancements such as smartphones, everything has become easily accessible. From social media to online banking, business information, and business applications, as well as online games for children. However, technological advancements have also led to an increase in crime and violations, including online transactions for narcotics, terrorist communication networks, and crimes such as gambling. This research uses a normative juridical research method, examining primary, secondary, and tertiary legal materials. The results show that the government can take several steps to prevent online gambling, including stricter law enforcement through site blocking and account suspension, digital platform monitoring, public awareness and education, and inter-agency and industry collaboration. The government has a strong legal basis to block online games like Roblox if they are proven to contain gambling elements. However, the effectiveness of such actions still faces several challenges. Ultimately, the government's legal certainty allows for decisive action against online games that facilitate gambling. Nevertheless, the success of online gambling eradication depends on a combination of strong regulation, careful law enforcement, and prevention strategies that focus on education and public awareness